Adsorption of Lead(II), Cadmium(II) and Copper(II) Ions on Agricultural Byproducts - Raghuwanshi, P.B.; Deshmukh, A.Y.; Doshi, A.G. (Asian Journal of Chemistry, 2010)
Adsorption of Pb2+, Cd2+ and Cu2+ on different agricultural byproducts has been measured at different temperatures. Adsorption of metal ions follows the order, polymerized orange skin < banana husk for Cd(ll) and Pb(II) and orange skin> banana husk for Cu(II). It could also be seen that Cu(lI) is a good adsorbing agent as compared to Cd(II) and Pb(II). Thermodynamic parameters have also been evaluated.